Monetary Persistence and the Labor Market: A New Perspective - Merkl, Christian; Lechthaler, Wolfgang; Snower, Dennis (Journal of Economic Dynamics & Control, 2010)
In this paper we propose a novel way to model the labor market in the context of a New-Keynesian general equilibrium model, incorporating labor market frictions in the form of hiring and firing costs. We show that such a model is able to replicate many important stylized facts of the business cycle. The reactions to monetary and real shocks become much more sluggish. Job creation and job destruction are negatively correlated. And the volatility of unemployment is much larger than in the standard search and matching model.
WiSo-Import:2015-03-26:888
Keywords: Transformation; Monetary persistence; Labor market; Hiring and firing costs; Forschungsbericht 2010; Business cycle dynamics